2021
DOI: 10.1002/ppap.202100129
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of CF4 + O2 and C6F12O + O2 plasmas for reactive‐ion etching applications

Abstract: This work represents a comparative study of gas-phase parameters and reactive-ion etching kinetics for Si and Si and SiO 2 in CF 4 + O 2 and C 6 F 12 O + O 2 plasmas. An interest to the C 6 F 12 O gas is because it combines the low global warming potential (low environmental impact) and weakly studied dry etching performance. It was shown that the investigated gas systems showed similar effects of processing conditions on electron-and ion-related plasma parameters as well as on the densities of F and O atoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…This is consistent with the results from previous studies, which showed that the C 6 F 12 O gas etch rate is lower than the CF 4 gas etch rate. [ 12,13 ] However, as shown in Figure 4, as the mixing ratio of C 6 F 12 O gas increased, the etch rate of the ACL material decreased more than the decrease in the SiO 2 etch rate. Consequently, it was confirmed that the etch selectivity for the ACL material increased as the mixing ratio of C 6 F 12 O gas increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results from previous studies, which showed that the C 6 F 12 O gas etch rate is lower than the CF 4 gas etch rate. [ 12,13 ] However, as shown in Figure 4, as the mixing ratio of C 6 F 12 O gas increased, the etch rate of the ACL material decreased more than the decrease in the SiO 2 etch rate. Consequently, it was confirmed that the etch selectivity for the ACL material increased as the mixing ratio of C 6 F 12 O gas increased.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, recent research on etching technology using this gas has been conducted. [12,13] In this study, a HAR oxide etching process was performed using an ICP system with a low-frequency bias power system. The etching characteristics were investigated for HAR oxide patterns at 13.56 and 2 MHz bias power.…”
Section: Introductionmentioning
confidence: 99%